The Speech Surrogacy Systems of the Yoruba Dùndún and Bàtá Drums. On the Interface Between Organology and Phonology - González, Mariano; Oludare, Olupemi (Frontiers in Communication, 2022)
The present study explores the interdependence between organology and phonology in the Yoruba dùndún and bàtá drums. We analyze how the specific features of these drums, such as corpus shape, size, kind and number of membranes, and playing techniques are used to form single systems of speech surrogacy. The study relies on field recordings collected by the project in Lagos, Nigeria, in February 2020, featuring performances of original Yoruba sentences previously unknown to the informants. Observing how the intrinsic characteristics of language sounds (pitch, duration, intensity and spectrum) are addressed by means of the acoustic properties each of the studied drums, we conclude that these foster independent speech surrogacy systems. Alongside a consideration of native perspectives on speech surrogacy, we propose an understanding of drum languages as platforms capable of supporting the development of native theories on sound and language.